The Conditions for Successful Utilization of Free Trade – Is the Dominican Republic Ready for DR-CAFTA? - Prášilová, Petra; Lipka, David; Daza Aramayo, Lourdes Gabriela, 1983-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2011)
The Master's Thesis "The Conditions for Successful Utilization of Free Trade -- Is the Dominican Republic Ready for DR-CAFTA?" is concerned with the role of complementary policies and reforms in international trade by developing countries. The first part of the thesis explores policies and conditions that are claimed to be essential for successful utilization of free trade, and attempts to quantify minimal or maximal benchmarks as conditions for a developing country that wishes to liberalize its trade. The outcome of this section shows that most areas but not all of them provide the opportunity for benchmarking. In the second part of the thesis, the state of the economic and human development in the Dominican Republic as a signatory of controversial DR-CAFTA is analyzed. The aim is to answer the main thesis question on preparedness of the DR for the FTA with the United States of America. The comparison of benchmarks from the first part of the paper and the DR data shows that the Dominica Republic is capable of utilizing DR-CAFTA agreement; however, to maximize the benefits, it must undertake reforms in critical areas.
Vedoucí práce: David Lipka
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: hospodářská politika [obor dipl. práce]; diplomové práce; master's theses